External factors affecting investment decisions of companies - Piotr Bialowolski; Dorota Weziak-Bialowolska (Kiel Institute for the World Economy (IfW), 2013)
In this paper we attempt to investigate the importance of certain external factors on the investment decision among Polish companies. With the use of data from the tailored made Survey on Receivables we examine factors influencing investment decisions of companies in Poland, assess the relation between the branch and company size and importance of the factors and finally we determine the relative influence of these factors on the actual investment reductions. The results showed that first, although the problem of payment delays is the most important single reason determining the investment decisions of Polish companies, its importance decreases when analyzed simultaneously with other reasons. Second, there are two driving forces determining the investment decisions of Polish companies, namely macroeconomic factors and law-related factors with the relative importance of the former lower than the latter. Third, there is a positive association between the importance attached to factors influencing investment decisions associated with either macroeconomic or legal environment and the investment reductions, meaning that companies facing higher investment reductions are also more prone to notice and value the factors influencing these decisions.
Keywords: D92; G11; G31; 330; investment decisions; company; survey; structural equation modelling